Somerset Club, ca. 1860 - Hawes, Josiah Johnson (Tufts Archival Research Center, 2005)
Building at the northeast corner of Somerset and Beacon Streets. A street light is located in the foreground of the photograph. A wrought iron railing adorns one side of the building, while a fence encircles it at street-level. Two men stand in front of the steps leading to the Somerset Club entrance. A third man stands on the northwest corner of Somerset and Beacon Streets. Originally built by David Hinckley, 1810, and referred to commonly as the Hinckley House; purchased by the Somerset Club in 1852; also residence of John Lowell Gardner. Image is part of the Henry P. Curtis Collection. 7 in diameter (photo is round), 7 3/4 x 8 5/16 Photographs